THE INFLUENCE OF CURRENT RATIO, TOTAL ASSET TURNOVER, AND R&D INTENSITY ON RETURN ON COMPANY ASSET IN THE PHARMACY SECTOR LISTED ON IDX FOR THE 2018-2023 PERIOD - ,; ,; ,; , (Bilancia : Jurnal Ilmiah Akuntansi; Vol 8 No 3 (2024): Bilancia : Jurnal Ilmiah Akuntansi, 2024)
This research aims to analyze the influence of Current Ratio, Total Asset Turnover, and Research and Development (R&D) Intensity on Return on Assets. The population in this research are all pharmaceutical sector companies listed on the Indonesia Stock Exchange.  Meanwhile, the sample was 8 pharmaceutical companies using the purposive sampling method.  Secondary data was obtained from the Indonesian Stock Exchange and the official website of each company.  The independent variables used are current ratio, Total Asset Turnover, and R&D Intensity.  Meanwhile the dependent variable is Return on Assets.  The data analysis technique used is descriptive analysis and path analysis with SEM PLS.  The results of this research show that the current variable has a positive and significant effect on Return on Assets, while the total asset turnover and R&D intensity variables have a negative and insignificant effect on Return on Assets. Keywords: Current Ratio; Total Aset Turnover; Intensitas Research and Development (R&D); Return on Asset Penelitian ini bertujuan untuk menganalisis pengaruh Current Ratio, Total Aset Turnover, dan Intensitas Research and Development (R&D) terhadap Return on Asset. Populasi dalam penelitian ini adalah seluruh perusahaan sektor Farmasi yang terdaftar di Bursa Efek Indonesia.  Sedangkan sampel sebanyak 8 perusahaan farmasi dengan menggunakan metode purposive sampling.  Data sekunder diperoleh di Bursa Efek Indonesia dan website resmi masing-masing perusahaan.  Variabel independen yang digunakan adalah current ratio, Total Aset Turnover, dan Intensitas R&D.  Sedangkan variabel dependent adalah Return on Asset.  Teknik analisis data yang digunakan adalah analisis deskriptif dan analisis jalur dengan SEM PLS.  Hasil penelitian ini menunjukkan bahwa variabel current berpengaruh positif dan signifikan terhadap Return on Asset, sedangkan variabel total asset turnover dan intensitas R&D berpengaruh negative dan tidak signifikan terhadap Return on Asset. Kata Kunci: Current Ratio; Total Aset Turnover; Intensitas Research and Development (R&D); Return on Asset